P174 Utility Of Needle Aspiration In Patients With Primary Spontaneous Pneumothorax With Complete Lung Collapse: A Retrospective 5-year Study. (10th November 2014) - Ganaie, MB; Bikmalla, S; Afridi, MA; Khalil, MA; Hussain, IR; Haris, M
Abstract : Introduction: Primary spontaneous pneumothorax (PSP) is a common presentation. Despite being known for over 200 years, there is variation in definition criteria and treatment recommendations. Previous studies comparing needle aspiration (NA) with intercostal drain (ICD) for all primary spontaneous pneumothoraces requiring intervention including those with complete lung collapse have shown no difference in immediate success, early failure and recurrence rate. There is no separate treatment algorithm for PSP with complete lung collapse in the current British Thoracic Society pneumothorax guidelines. We aimed to compare NA with ICD as the first intervention in this sub-group. Methods: We conducted a retrospective observational study of 735 consecutive pneumothorax episodes between March 2008 and December 2013. Those with secondary spontaneous pneumothorax, history of trauma and iatrogenic pneumothorax were excluded. Pneumothorax with no visible aerated ipsilateral lung on plain chest radiograph was defined as 'PSP with complete lung collapse'. Patient case records and plain chest radiographs were reviewed. Values of p < 0.05 were considered statistically significant. Results: Of the 735 episodes, 233 (32%) were PSP. 61 PSP patients were identified to have complete lung collapse on chest radiograph. 32 patients had NA and 29 ICD as the first intervention. There was no statistically significant difference between the two groups in terms of age, sex, smoking history and symptoms. Compared to the NA group, patients with ICD had significantly better immediate success rate (66% vs. 10%; p < 0.0001) and lower rate of recurrence (3% vs. 31%; p = 0.0064). Median length of stay was similar in both groups. Almost a third of the patients in both groups required a definitive surgical intervention. Conclusion: Our results suggest significantly better success with ICD as the first intervention in the management of PSP with complete lung collapse and there was no added benefit of NA. We propose a further sub group of PSP with complete lung collapse in which NA should not be attempted.